The Impact of the Medicare Hospital Readmission Reduction Program in New York State. Issue 2 (February 2016) - McGarry, Brian E.; Blankley, Albert A.; Li, Yue
Abstract : Background: Medicare's Hospital Readmission Reduction Program (HRRP) created clear financial incentives for hospitals to prevent readmissions. Although existing evidence suggests readmission rates have been declining, the direct contribution of this policy to these reductions is unclear. Furthermore, it is unknown whether HRRP has produced unintended effects, including the substitution of outpatient hospital care for readmissions. Objectives: To determine the effect of HRRP in New York State on both the likelihood of being readmitted and returning to hospital emergency department (ED) care within 30 days of discharge. Research Design: Difference-in-difference estimation using prepolicy and postpolicy hospital claims data and the proportion of a hospital's inpatient revenue at risk for HRRP penalization to identify policy exposure. Policy effects are estimated using multivariate logistic regressions. Results: We find significant global reductions in readmissions in the postpolicy years, but no evidence of a differential policy effect on patients discharged from hospitals at risk for proportionally larger HRRP penalties in either postpolicy year 1 [adjusted odd ratio (AOR) =1.00, P =0.733] or 2 (AOR=1.01, P =0.315). HRRP did increase the odds of patients from hospitals facing greater financial risk having a 30-day ED visit in both postpolicy years (AOR=1.04, P =0.009 and AOR=1.07, P <0.001). Conclusions: Our findings suggest that while readmissions have decreased in New York State, these declines may not be directly attributable to HRRP penalties. The policy did produce significant potentially unintended effects in the form of greater postdischarge ED utilization among facilities facing proportionally larger penalties.